PENGARUH BIMBINGAN MENTAL PADA IBU PASCA PERSALINAN TERHADAP PENINGKATAN PERKEMBANGAN PERILAKU BIOPSIKOSOSIAL NEONATUS - Maria Terok; Max Wungkana (POLTEKKES KEMENKES MANADO, 2012)
Neonatus condition of mothers is very susceptible and easily disturbed. However, the development ofbiopsychosocial behaviour is very fast when mothers start early stimulation since childbirth(Notosoedirdjo and Latipun, 2007). Stimulation which is fast, accurate and intensive will increase braindevelopment by 50% at the age of the first six months after childbirth (Joseph, 2007). This research isaimed to develop neonatus biopsychosocial behaviour through an approach that gives mental guidance ofboth motoric cognitive skills and affective cognitive skills to mothers. This research is a QuasyExperimental Design with pretest and post test control group. The population of the reseach is mothersafter childbirth together with their babies that qualify both the inclusive and exclusive criteria, totalling 24mothers pairing with their babies taken as total sample. They are then divided at random into two groupsnamely the experimental and the control groups with 12 mothers each pairing with their babies. The datawas collected by way of an interview and a questionaire of the Neonatal Behaviour Assessment Scale(NBAS) and a scale of the mothers’ bounding behaviour to their babies. The result of the data analysisshowed a significant effect on the mental guidance given to mothers after childbirth on the increase of thedevelopment of neonatus biopsychosocial behaviour. The neonatus biopsychosocial behaviour wasincreased by a value of p 0,002 < α = 0,05. Other proof was the increase of the development of neonatusbiopsychosocial behaviour from the NBAS score by 42,32%. There was an increase in the weight of thebabies by 8,7%, an increase in the length of the babies by about 1,98% and an increase in the circle of thebabies’ heads by 2,49% from the scores obtained before intervention to the experimental group. A verysignificant effect was found on the increase of the development of the mothers’ bounding behaviour totheir babies, as a result of the mental guidance given to them, by the value of p 0,000 < α = 0,05. Asupporting proof was the increase in the score of the mothers’ bounding behaviour to their babies by50,14% from the score before intervention to the experimental group